2019
DOI: 10.1016/j.msard.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Use of coping strategies in multiple sclerosis: Association with demographic and disease-related characteristics✰

Abstract: Highlights People with MS mostly utilise a mix of active problem-and emotion-focused coping strategies  Older age, presence of a partner and shorter disease duration associated with adaptive strategies  Younger age, being male and having RRMS are associated with higher Substance Use  Being female associated with greater use of emotion-focused strategies  Unemployment and greater disability associated with higher use of avoidance strategies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
6
33
2
Order By: Relevance
“…The finding that both the Very High morning and evening fatigue groups used self-blame as a coping strategy is consistent with prior research that identified self-blame as a predictor of fatigue in new parents [46], as well as in patients with melanoma [47], multiple sclerosis [48], and breast cancer [49]. In contrast, self-compassion was identified by patients with ESKD as an effective intervention to decrease their selfblame when they needed to ask for support to cope with their fatigue [44].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The finding that both the Very High morning and evening fatigue groups used self-blame as a coping strategy is consistent with prior research that identified self-blame as a predictor of fatigue in new parents [46], as well as in patients with melanoma [47], multiple sclerosis [48], and breast cancer [49]. In contrast, self-compassion was identified by patients with ESKD as an effective intervention to decrease their selfblame when they needed to ask for support to cope with their fatigue [44].…”
Section: Discussionsupporting
confidence: 87%
“…As an emotion-based coping strategy, venting refers to focusing on and expressing negative feelings [17]. While not evaluated in oncology patients, venting was found to increase patients' ability to cope with both positive and negative feelings about multiple sclerosis [48] and may warrant evaluation as a strategy for fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The data analysis showed that MS patients most often used the strategies of seeking emotional support (2.11) and active coping (1.96). The studies by Holland et al 73 and Cornero Contentti et al 74 show that the most commonly applied strategies included acceptance and active coping. On the other hand, the least frequently used mechanisms were turning to religion (0.48) and substance use (0.6), which was confirmed in studies by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Chronster and Chan [39] place a sense of self-mastery, control, self-efficacy, and interpersonal skills among internal coping resources, and social support and material goods among external ones. Holland et al [40] found the most commonly coping strategies in patients with MS Acceptance, Active Coping, Planning and Positive Reinterpretation and Growth. Coping strategies have been identified as an important predictor of quality of life in patients with MS [41, 42].…”
Section: Discussionmentioning
confidence: 99%